2016
DOI: 10.17795/semj38462
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review and Meta-Analysis of the Prevalence of Anemia Among Pregnant Iranian Women (2005 - 2015)

Abstract: Context: Anemia is a common, global health problem that has short-term and long-term effects during pregnancy. Several studies have been conducted on the prevalence of anemia among pregnant Iranian women in the last 10 years (2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015). The current study evaluated the prevalence of anemia among pregnant Iranian women in this time period.Evidence Acquisition: The current study followed the Preferred Reporting Items for systematic reviews and meta-analyses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Pregnancy has profound physiological effects on thyroid gland function [9]. During pregnancy, the thyroid gland size increases by 10% in countries with adequate iodine and to a greater extent in countries with iodine deficiency [10].…”
Section: Introductionmentioning
confidence: 99%
“…Pregnancy has profound physiological effects on thyroid gland function [9]. During pregnancy, the thyroid gland size increases by 10% in countries with adequate iodine and to a greater extent in countries with iodine deficiency [10].…”
Section: Introductionmentioning
confidence: 99%
“…Globally, thirty-two million four hundred thousand (38.2%) pregnant women were found to anemic [3]. A systematic review conducted in Iran showed that the prevalence of anemia was 17.9% [4]. Its burden became worth in developing countries which was 48.7% in South East Asia and 46.3% in Africa [3].…”
Section: Introductionmentioning
confidence: 99%
“…There are many physiological effects of pregnancy on thyroid gland function. 8 The countries where iodine is adequate, the thyroid gland's size increases by 10% during pregnancy, whereas it may increase to a greater extent in countries where there is a deficiency of iodine. 9 during pregnancy, deficiency of thyroid hormone and requirement of iodine both exacerbates by 50% approximately as part of physiology.…”
Section: Introductionmentioning
confidence: 99%